The Effect of Live Streaming, Promotions, and Viral Marketing on Shopee Purchasing Decisions among College Students - Bakti, Marsita Julia; Sari, Dhani Efita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Currently, there are many e-commerce platforms used to sell online, one of which is Shopee. Shopee offers a live-streaming feature with various promotions. The promotion is spread through a form of social media marketing known as viral marketing. This study aims to determine the effect of live streaming, promotions, and viral marketing on purchasing decisions at Shopee for students. This study uses quantitative research methods with a causal-comparative design. The sample in this study consisted of 187 accounting education students, at Universitas Muhammadiyah Surakarta. Sampling was done using simple random sampling, and data collection was carried out by distributing questionnaires. The results of this study indicate that the F-test (simultaneous) and t-test (partial) show that live streaming has a significant effect on purchasing decisions, promotion has a significant effect on purchasing decision variables, viral marketing has a significant effect on purchasing decision variables, and live streaming, promotion, and viral marketing have a significant effect on purchasing decisions.